Formação continuada e adaptações curriculares na escola do/no campo: percepção dos professores dos anos iniciais do ensino fundamental - Mota, Luciene Sandes (2025)
The dissertation Continuing Education and Curriculum Adaptations in Rural Schools: Teachers’ Perceptions in the Early Years of Elementary Education presents the results of a study conducted with teachers working from the 1st to the 5th grade of elementary school. The research was carried out in a municipal institution located in the rural area of Porto Feliz, in the interior of São Paulo state, with the participation of five teachers. A quantitative-qualitative approach was adopted, combining elements of both methodologies to provide a more comprehensive analysis of the phenomenon under investigation. The central aim was to investigate teachers’ perceptions of continuing education and curriculum adaptations implemented to meet the specificities of rural education. The study sought to answer the following question: What are the perceptions of teachers working in the early years of elementary education in a public school located in the rural area of Porto Feliz regarding continuing education and the curriculum adaptations made to address the particularities of rural education? The specific objectives included understanding how continuing education takes place for teachers working in rural schools, focusing on their own perceptions; identifying the need for curriculum adaptations that take into account the unique characteristics of these institutions; and analyzing how the particularities of rural life are perceived and integrated both into the curriculum and into teacher education. The instruments for data collection included: a literature review on Rural Education and continuing teacher education; a questionnaire to obtain preliminary information about participants’ training; narrative interviews; and document analysis. The research findings reveal that the school curriculum is predominantly limited to modifications made by teachers, based on the official curriculum guidelines of the Municipal Department of Education. There is a noticeable lack of opportunities for the effective integration of themes that foster socio-educational practices, which could enhance the value of the traditional knowledge of rural families and their ways of life. In addition, no continuing education programs tailored to the specific needs of teachers working in this context were identified. This scenario highlights a pedagogical organization in rural schools that diverges from the formative demands required to respect local identities. By analyzing the perspectives of teachers in a rural school in Porto Feliz on their professional development and curriculum adaptations, this study provides insights to improve pedagogical practices and to formulate educational public policies that are better suited to the needs of the rural context. By valuing teachers’ experiences as a source of knowledge, it contributes to building a more just and inclusive rural education.